Effect of Confinement on the Structural, Dielectric, and Dynamic Properties of Liquid Crystals in Anopores - Pavel V. Maslennikov; Alex V. Zakharov (Liquids)
Based on data from broadband dielectric spectroscopy (BDS) and a molecular model based on the Landau–de Gennes concept, the effect of confinement on the structural, dielectric, and dynamic properties of 4-n-pentyl-4′-cyanobiphenyl (5CB) in the nematic phase is studied. The dielectric permittivity and relaxation times were previously obtained by the BDS technique in a wide frequency range (<semantics>1<mspace width="3.33333pt"></mspace>MHz≤f≤1<mspace width="3.33333pt"></mspace>GHz</semantics>) in the nematic phase composed of 5CB molecules confined to Anopore membranes with pore sizes of 0.2 <semantics>μ</semantics>m. The distance-dependent values of the order parameter <semantics>P2(r)</semantics>, the relaxation time <semantics>τ(r)≡<msubsup>τ001</msubsup>(r)</semantics>, the rotational diffusion coefficient <semantics>D⊥(r)</semantics>, and both rotational viscosity coefficients <semantics>γi(r)</semantics> (<semantics>i=1,2</semantics>) as functions of the distance r away from the bounding surface are calculated by a combination of existing statistical-mechanical approaches and data obtained by the BDS technique. Reasonable agreement between the calculated and experimental values of <semantics>γi<mspace width="3.33333pt"></mspace>(i=1,2)</semantics> for bulk 5CB is obtained.